Sistem Informasi Penjualan Obat Pada Apotek Wi.Ly Berbasis Local Hosting - Sally Sally (Mahesa Research Institute, 2023)
With the rapid development of information technology, it has a very important role in various fields. The purpose of this thesis research is to produce the development of a systematic and structured data collection, sales, purchasing system at Willy's Pharmacy, where the previous system still used a manual system with using books, so the author can use local hosting-based information systems as data storage media. The results of the system are made to facilitate the sales and purchase process. The author's purpose in making this research is to make it easier for Willy Farma pharmacies to check, record sales, report sales, purchase reports on drugs. In addition, by using local web hosting, data information can be accessed at any time. The information system is in the form of Local hosting with the Xampp.